SUBJECTIVE EVALUATION OF CONDITIONS OF TENSION AND OCCUPATIONAL HEALTH JOBS ROLLING PRODUCTION - Смагулов, Нурлан Кемельбекович; Хамитов, Тулеген Нургалиевич (Medicine in Kuzbass, 2018)
Subject of research. In assessing the functional status of working in a production environment along with objective research is also needed subjective indicators, namely, to survey employees about the nature of work, level of fatigue, time of its occurrence, the lifestyle of the workers, etc.Purpose of work – subjective evaluation of working conditions and health of workers rolling production.Method of research. To study the characteristics of the workers the survey was conducted, including the list of issues of hygiene, a professional graphic and psychological nature of mode of work and rest, health. Statistical processing was carried out by calculating the proportion of identical answers to the same question.Main results. It was revealed that a group of workers, directly associated with the production process of rolling metal (basic working skills), and therefore to a greater extent in contact with the unfavorable factors of production environment, most appreciate the working conditions as poor than workers engaged in repair and installation of equipment. The level of work organization at the workplace the majority of respondents assessed as satisfactory, although most believe their workplace is uncomfortable, work is required during the work shift concentration, eyestrain. 41.6 % of its efficiency noted as average, and only 33.4 percent as high. Health status the majority of respondents rated as satisfactory to 43.8 % as good or 29.8 %, bad – 26,4 % of the respondents.Conclusion. The survey showed that if the subjective evaluation of working environment factors and labor process corresponds to the results hygiene-ergonomic research, the assessment of the health showed its bias, as evidenced by the results of analysis of morbidity.
Keywords: workers; sheet rolling production; questionnaire; subjective assessment